Problems regarding the constitutionalization of multiculturalism: an anthropological perspective - Miloš Milenković (Etnoantropološki Problemi, 2008)
In this article, from an anti-essentialist and anti-primordial view, of normal science in anthropology, argumentation is being developed against an essentialist foundation of multiculturalism, as an imprudent legal transplant and as a mode of developing/survival of ethnocratic professionalizing of ethnicity and the policy of identity, through the example of a symptomatic article 64 paragraph 2 of the Constitution of the Republic of Serbia. The Constitution radicalizes multicultural policies, treating ethnic, confessional and other contingent arrangements as natural classes. Treating the cultural-historic categories, for example, ethnicity or confessional (religious) identity, as natural classes in public policies like the Constitution, leads to a situation where the contingent, interactive arrangements in the cultural reality receives an aureole of a given, indifferent and permanent states, which potentially generates and deepens social conflicts which it intends to absorb, forestall or regulate. After referring to the proven comparatively-historic contraindicated aspects of multicultural policies and a shorter analysis of the above mentioned example, the author argues for deepening of the productive interdisciplinary cooperation of professional lawyers, professional anthropologists and other experts in the field of social-humanistic sciences, in a mutual effort for further de-primordialisation and de-essentialisation of public policies in Serbia.